STRENGTHENING IMAGE OF PRESIDENTIAL CANDIDATES THROUGH POLITICAL DISCOURSE ON INSTAGRAM SOCIAL MEDIA: PENGUATAN CITRA KANDIDAT PRESIDEN MELALUI WACANA POLITIK DI MEDIA SOSIAL INSTAGRAM - Hanina Al Anan Awang Rif; Sri Wahono; Sukarno Sukarno (LLDIKTI Wilayah X, 2024)
This research explores the 2024 Presidential Election advertisements on Instagram using Fairclough's theoretical approach. The main focus is analyzing advertising texts, discourse practices, and the social context involved in the production and dissemination process of these advertisements. The aim of the research is to understand how political advertising on social media platforms such as Instagram influences public perception and utilizes the dynamics of globalization in the context of presidential elections. Research methods involve text analysis to understand the narrative used in the advertisement, discourse practice analysis to explore the communication strategies used, and social analysis to understand the social and political impact of the advertisement. The results of this research provide in-depth insight into the role of social media in contemporary political campaigns, as well as its implications for democracy and public political participation.